IMPROVING STUDENTS’ READING COMPREHENSION THROUGH STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TECHNIQE - Sapriani, Lita; Suhartono, Luwandi; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was aimed to know how STAD technique improves the eighth grade students’ reading comprehension at SMP Negeri 21 Pontianak in academic year 2017/2018. It was a classroom action research which was conducted in two cycles. Each cycle consisted of four components namely planning, acting, observing and reflecting. The research instruments were observation in form of observation checklist and field notes in order to describe the process while applying STAD technique in the classroom. In addition, she used measurement technique in form of reading test items to measure students’ achievement. These reading test items including five aspects that helps students to improve their reading comprehension. These five reading aspects in terms of identifying main idea, identifying specific information, identifying reference, identifying inference and vocabulary. The result of this study that, the students improved their reading comprehension through STAD technique by discussing the issues proposed by the teacher in the reading text. Further more, they worked together in heterogeneous teams to get higher improvement point as their goal in each cycle. This condition created the compotitive athmosphere in the classroom. So, it increased students’ motivation to comprhened the reading text.Keywords: Reading Comprehension, Classroom Action Research, STAD Technique